Connecting the Aracuai and Ribeira belts (SE - Brazil): Progressive transition from contractional to transpressive strain regime during the Brasiliano orogeny - Egydio-Silva, Marcos; Vauchez, Alain; Fossen, Haakon; Goncalves Cavalcante, Geane Carolina; Xavier, Bruna Catarino (Journal of South American Earth Sciences, 2018)
International audience Whether the Araçuaí and the Ribeira Neoproterozoic belts in southeast Brazil represent a continuous or two distinct orogenic belts is still a debated question. We compile existing geologic and geophysical data and argue that the two belts, in spite of differences in tectonic style and kinematics, should be considered as part of an orogenic continuity that formed during the mostly Late Proterozoic Brasiliano orogenic evolution. Structural mapping supported by Anisotropy of Magnetic Susceptibility data shows that the transition between the two belts is gradual, with a progressive change from a NE-trending subvertical foliation and subhorizontal stretching lineation in the Ribeira belt to gently dipping and less pronounced fabrics in the Araçuaí belt. The lineation progressively changes northward from NE to E-W, suggesting a transition from overall transcurrent to thrust kinematics, and the solid-state finite strain seems to get progressively higher into the Ribeira belt. Differences in tectonic style are explained by the southward termination of the rigid São Francisco craton, which caused oblique collision and lateral escape, as supported by numerical modeling. Shear-wave splitting measurements suggest that the transcurrent deformation in the Ribeira belt affected the entire lithosphere. In the transitional zone, the seismic anisotropy pattern is more complex and the delay time between the fast and slow shear-waves is smaller. These observations, together with a similar record of magmatism and timing of orogenic events and P-T conditions during peak metamorphism strongly support continuity between the Araçuaí and the Ribeira belts. This model is a "quasi-facsimile" of the Paleoproterozoic deformation that occurred in the Great Slave Lake area in Canada.